Balinese Musical Composition Surya Candra | Komposisi Karawitan Bali Surya Candra - I Putu Ono Putra; Putu Tiodore Adi Bawa (GHURNITA: Jurnal Seni Karawitan, 2021)
Phenomena are extraordinary things in life on earth and can occur at any time for example day and night. The time of day when the sun is visible, and night is marked by the absence of the sun in the sky but replaced by the presence of the moon, therefore, between day and night it is impossible to unite but separate from each other or occur alternately and not simultaneously. The sun and the moon symbolize the difference in character with the existence of day and night, and in Balinese terms the sun and moon are called Surya Candra. The objectives of this work are: to raise natural phenomena as ideas to be used as works of art for kekebyaran percussion compositions entitled Surya Candra. In realizing Surya Candra's percussion work, the creator borrowed the concept of the creation process proposed by Alma M.Hawkins because this method is very appropriate in realizing Surya Candra's work, this method states that there are three stages of the creation process in creating art, namely the exploration stage, improvisation, and forming. This work is in the form of a kekebyaran percussion with the title Surya Candra.